Identifying Advanced Biotechnologies to Generate Biofertilizers and Biofuels From the World’s Worst Aquatic Weed - Ezzariai, Amine; Hafidi, Mohamed; Ben Bakrim, Widad; Kibret, Mulugeta; Karouach, Fadoua; Sobeh, Mansour; Kouisni, Lamfeddal (Frontiers in Bioengineering and Biotechnology, 2021)
Water hyacinth (Eichhornia crassipes L.) was introduced as an invasive plant in freshwater bodies more particularly in Asia and Africa. This invasive plant grows rapidly and then occupies a huge layer of freshwater bodies. Hence, challenges are facing many countries for implementing suitable approaches for the valorization of the world's worst aquatic weed, water hyacinth (WH). A critical and up-to-date review article has been conducted for more than one year, based on more than 100 scientific journal articles, case studies, and other scientific reports. Worldwide distribution of WH and the associated social, economic and environmental impacts were described. In addition, an extensive evaluation ofthe most widely used and innovative valorization biotechnologies, leading to the production of biofertilizer and bioenergy from WH, was dressed. Furthermore, an integrated search was used in order to examine the related advantages and drawbacks of each bioprocess, and future perspectives stated. Aerobic and anaerobic processes have their specific basic parameters, ensuring their standard performances. Composting was mostly used even at a large scale, for producing biofertilizers from WH. Nevertheless, this review explored some critical points to better optimize the conditions (presence of pollutants, inoculation, duration) of composting. WH has a high potential for biofuel production, especially by implementing several pretreatment approaches. This review highlighted the combined pretreatment (physical-chemical-biological) as a promising approach to increase biofuel production. WH valorization must be in large quantities to tackle its fast proliferation and to ensure the generation of bio-based products with significant revenue. So, a road map for future researches and applications based on an advanced statistical study was conducted. Several recommendations were explored in terms of the choice of co-substrates, initial basic parameters, pretreatment conditions and all crucial conditions for the production of biofuels from WH. These recommendations will be of a great interest to generate biofertilizers and bioenergy from WH, especially within the framework of a circular economy.